2017
DOI: 10.1021/acs.est.6b04700
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aerosol Liquid Water in Secondary Organic Aerosol Formation from Volatile Organic Compounds

Abstract: A key mechanism for atmospheric secondary organic aerosol (SOA) formation occurs when oxidation products of volatile organic compounds condense onto pre-existing particles. Here, we examine effects of aerosol liquid water (ALW) on relative SOA yield and composition from α-pinene ozonolysis and the photooxidation of toluene and acetylene by OH. Reactions were conducted in a room-temperature flow tube under low-NO conditions in the presence of equivalent loadings of deliquesced (∼20 μg m ALW) or effloresced (∼0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
113
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 75 publications
12
113
0
1
Order By: Relevance
“…This was attributed to the aqueous partitioning and subsequent reactions in ALW of smaller photooxidation products, such as glyoxal (Faust et al, 2017). Our results suggest that the increase in the SOA yield due to the ALW-supported chemistry is at least partly counteracted by the lower yield of oligomers under high-RH conditions.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…This was attributed to the aqueous partitioning and subsequent reactions in ALW of smaller photooxidation products, such as glyoxal (Faust et al, 2017). Our results suggest that the increase in the SOA yield due to the ALW-supported chemistry is at least partly counteracted by the lower yield of oligomers under high-RH conditions.…”
Section: Discussionmentioning
confidence: 71%
“…In previous studies on the effect of RH on SOA yield from toluene in the presence of hygroscopic seed Kamens et al, 2011;Faust et al, 2017;Liu et al, 2017;Jia and Xu, 2017), an opposite effect was observed in which the SOA yield increased at high RH. This was attributed to the aqueous partitioning and subsequent reactions in ALW of smaller photooxidation products, such as glyoxal (Faust et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…3b and 3c for Case-2 verify this conclusion as well. Besides, an ambience with high relative humidity (RH) is favorable for the increase of PM2.5 concentration in the ABL through secondary formation by heterogeneous reactions (Quan et al, 2015;Wang et al, 2012;Faust et al, 2017) and hygroscopic growth (Engelhart et al, 2011;Petters and Kreidenweis, 2008). For Case-1, the RH during the CS keeps high with a mean value of 53% but sharply 25 falls into a very low level once entering the TS.…”
Section: Methodsmentioning
confidence: 99%